UNDERSTANDING SELF-CONFIDENCE IN RURAL ADOLESCENT WITH PSYCHOSOCIAL PROBLEMS - Sigit Hendrawan Wicaksono; Mimbar Oktaviana (International Conference on Psychology and Education (ICPE), 2025)
Self-confidence is a crucial psychological factor that influences adolescents' ability to participate socially and overcome academic and emotional challenges. This study uses a qualitative case study approach involving in-depth interviews and direct observation of a 17-year-old high school student in a rural area of Lamongan. Data were collected from the student, parents, and peers, then analyzed thematically to explore patterns related to self-confidence. The findings reveal four dominant themes: low social validation at school, authoritarian and emotionally distant parenting, dependence on external support, and negative academic self-perception. The subject's self-confidence only increased in an emotionally safe environment. These results indicate that the self-confidence of the subjects studied in a rural context is influenced by interpersonal dynamics and self-concept. These findings are contextual to one case and cannot be generalized, but they provide valuable insights into the importance of emotional support in shaping the self-confidence of rural adolescents.